Virtual Physical Education During COVID-19: Exploring Future Directions for Equitable Online Learning Tools - D'Agostino, Emily M.; Urtel, Mark; Webster, Collin A.; McMullen, Jaimie; Culp, Brian (Frontiers in Sports and Active Living, 2021)
Introduction: School closures prompted by the COVID-19 pandemic reduced opportunities for US youth to be physically active and disproportionately impacted health disparities in this population. Physical education provides the largest intervention to support the physical activity of school-aged youth, but teachers' opinions about how to maintain quality programming during virtual learning periods remain unexplored. Applying a diversity, equity and inclusion framework, this study explored physical education teachers' perceived significance of different design features for an online teaching tool to promote physical activity equity during school closures. Methods: Previous literature and focus groups informed the development of a survey administered in summer/fall 2020. Survey participants (n = 60) were physical education teachers from 400 randomly selected US preschool-12th grade schools drawing from a national database. Participants rated the significance of four design features in relation to five key attributes of an online supplement to in-person physical education programs. One-way ANOVAs were used to assess differences in teachers' ratings by demographic characteristics. Results: Between-group differences were found in teacher ratings of design features related to the usability, accessibility, equitability, and formal assessment capabilities of an online physical education tool. Differences were based on teacher gender, school level, and geographic location. Conclusions: Future research to promote physical activity equity among preschool-12th grade youth should examine tailored virtual physical education learning tools that address what teachers perceive to be the most significant design features to support equitable physical education among diverse student groups.